Population study of causes, treatment, and outcome of infertility. Issue 6510 (14th December 1985) - Hull, M G; Glazener, C M; Kelly, N J; Conway, D I; Foster, P A; Hinton, R A; Coulson, C; Lambert, P A; Watt, E M; Desai, K M
Abstract : Specialist infertility practice was studied in a group of 708 couples within a population of residents of a single health district in England. They represented an annual incidence of 1.2 couples for every 1000 of the population. At least one in six couples needed specialist help at some time in their lives because of an average of infertility of 21/2 years, 71% of whom were trying for their first baby. Those attending gynaecology clinics made up 10% of new and 22% of all attendances. Failure of ovulation (amenorrhoea or oligomenorrhoea) occurred in 21% of cases and was successfully treated (two year conception rates of 96% and 78%). Tubal damage (14%) had a poor outlook (19%) despite surgery. Endometriosis accounted for infertility in 6%, although seldom because of tubal damage, cervical mucus defects or dysfunction in 3%, and coital failure in up to 6%. Sperm defects or dysfunction were the commonest defined cause of infertility (24%) and led to a poor chance of pregnancy (0-27%) without donor insemination. Obstructive azoospermia or primary spermatogenic failure was uncommon (2%) and hormonal causes of male infertility rare. Infertility was unexplained in 28% and the chance of pregnancy (overall 72%) was mainly determined by duration of infertility. In vitro fertilisation could benefit 80% of cases of tubal damage and 25% of unexplained infertility--that is, 18% of all cases, representing up to 216 new cases each year per million of the total population.